A Case of Type 2 MI with Normal Coronary Arteries: Case Report & Literature Review - Anwar, AFM Azim; Mumu, Sanjida Anjum; Islam, Azharul; Khaled, Md Fakhrul Islam; Ahmed, Khurshed; Hoque, Md Harisul (University Heart Journal, 2022)
Clinicians have long recognized that acute myocardial infarction (MI) can occur in the absence of atherothrombosis . The Universal Definition of MI Global Taskforce introduced a classification system in 2007 (and reaffirmed in 2012) that defined type 2 MI (following standard diagnostic criteria) as MI occurring due to an imbalance in myocardial oxygen supply and/or demand not caused by atherosclerotic plaque disruption. Nevertheless, ambiguity remains regarding how to diagnose type 2 MI and how to distinguish it from both type 1 MI and myocardial injury. Here we report a case of a 23 year old young woman attended to emergency department, with typical chest pain and shortness of breath for 6 hours, Diarrhoea for 2 days, and single time loss of consciousness for 5 minutes, 6 hours before attending to hospital. Cardiac enzymes were rising titres in subsequent samples, Serum Creatinine was also high. Echocardiography performed 36 hour later, showed no regional wall motion abnormality, coronary angiogram showed normal coronary arteries. So, a diagnosis of Myocardial Infarction (Type 2 MI) with Non Obstructive Coronary Artery (MINOCA) was made, and MINOCA was attributed to hypovolemic shock (resulting from Dirrrahoea), manifested as MI, Syncope and AKI. University Heart Journal 2022; 18(2): 128-131